New Hypothesis on Pathogenesis of Ovarian Cancer Lead to Future Tailored Approaches. (25th August 2013) - Rescigno, P.; Cerillo, I.; Ruocco, R.; Condello, C.; De Placido, S.; Pensabene, M.
Abstract : In the last decades, management of epithelial ovarian cancer (EOC) has been based on the staging system of the International Federation of Gynecology and Obstetrics (FIGO), and different classifications have been proposed for EOC that take account of grade of differentiation, histological subtype, and clinical features. However, despite taxonomic efforts, EOC appears to be not a unique disease; its subtypes differ for epidemiological and genetic risk factors, precursor lesions, patterns of spread, response to chemotherapy, and prognosis. Nevertheless, carboplatin plus paclitaxel combination represents the only standard treatment in adjuvant and advanced settings. This paper summarizes theories about the classification and origin of EOC and classical and new prognostic factors. It presents data about standard treatment and novel agents. We speculate about the possibility to create tailored therapy based on specific mutations in ovarian cancer and to personalize prevention.